Factors Affecting Yemeni University Students’ Translation Using Google Translate - Salem, Reham Derhim H; Ahmed, Waleed Mohammed A. (University of Science and Technology, Sana'a, 2024)
The engagement of Yemeni undergraduate students in an effective translation process using machine translation (MT) including Google translate (GT) seems to be affected by certain factors which may have positive or negative effect on the translation of Arabic texts into English. This study aimed to explore factors affecting Yemeni undergraduate students' translation of Arabic texts into English when using GT. To achieve this objective, a qualitative approach was employed by means of an interview to gather data from students about factors that may affect their translation. Collected data were analyzed following a thematic analysis method. Findings revealed fostering and impeding factors that affect students' translation when using GT. Fostering factors included positive attitude toward MT, awareness of GT limitations, dissatisfaction with GT translations and think-aloud strategy. On the contrary, impeding factors involved challenges faced by participants, lack of competence in using GT, negative effect of think-aloud and negative attitude toward GT. The study provides insights to educators about what may affect students' translation using GT which can be considered in training translation students on how to use GT effectively. Future research could examine factors that may affect students' use of other machine translation tools, including artificial intelligence (AI).
Keywords: Google Translate (GT); machine translation (MT); factors affecting translation; undergraduate translation students; qualitative approach